A Comprehensive Review of Crop Disease Identification Through Modern Artificial Intelligence Technology - Tandan, Gajendra; Ambhaikar, Asha (International Journal of Computer Sciences and Engineering, 2024)
India is a developing country. The 65% of India`s people live in villages, whose main occupation is agriculture. India has certainly made progress in the field of information technology. The IT advancement and technology is direct impact on agriculture. After the advent of the 21st century, modern agricultural technology got a boost in India. In the present era, farmers are moving towards farming using modern and scientific methods. AI based technology is the foundation of modern technology. Equipped with modern equipment and applications for prevention of pests and diseases in crops. The AI technology quickly and speedily identify the diseases occurring in crops can very easily treated with accuracy high accuracy. In this review, we have studied a lot of AI and their sub-domain machine learning (ML) method application in agriculture, especially on crop leaf diseases. ML technology can be used to identify leaf disease in the captured images.